FUNDRAISING ON THE CONSTRUCTION OF A MOSQUE IN PERSPECTIVE OF INFAK AND SEDAKAH CONTRACTS: A study at the Great Mosque of Al-Falah, Pidie Regency - Wandi, Sulfan (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2022)
Infaq and alms can not only be given to one individual but can also be distributed for social purposes such as the construction of mosques, one of which is the Al-Falah Great Mosque of Pidie Regency which was built in 2015 and is currently still under construction. one of the efforts to launch in the financial sector the development committee carried out fundraising activities. in the fundraising activities carried out by the mosque construction committee, there is a suspicion of transparency in the use of funds, so it is feared that the accountability of these funds will be ineffective. As for what this research is about, the first is how the strategy is carried out by the mosque construction committee to obtain development funds. secondly how this fundraising activity was able to generate funds for the construction of the Great Mosque in accordance with the target and third how the success of the infaq and alms fundraising carried out by the mosque construction committee for the construction of the Great Mosque of Alfalah, Pidie Regency. This study used a descriptive method, and data collection was obtained through field research with interviews and documentation. the results obtained from this study found that the infaq and alms fund collection system was obtained through deductions from the salaries of civil servants in the Pidie area, but the infaq and alms funds that had been collected had not been budgeted for the construction of mosques. in this case the author concludes that there is no fundraising effort that is applied by the mosque construction committee to persuade the community to give infaq and alms each year according to the specified target.